Finite-time projective synchronization of fractional-order delayed quaternion-valued fuzzy memristive neural networks - He, Yan; Zhang, Weiwei; Zhang, Hai; Cao, Jinde; Alsaadi, Fawaz E. (Nonlinear Analysis: Modelling and Control, 2024)
In this paper, the finite-time projective synchronization (FTPS) problem of fractionalorder quaternion-valued fuzzy memristor neural networks (FOQVFMNNs) is studied. Through establishing a feedback controller with signed functions and an adaptive controller, sufficient conditions for FTPS for FOQVFMNNs are obtained. Furthermore, the synchronization establishment time is calculated. Finally, the practicability of the conclusions is verified by numerical simulations.